2010
DOI: 10.1111/j.1939-0025.2010.01026.x
|View full text |Cite
|
Sign up to set email alerts
|

Rates and impact of trauma and current stressors among Darfuri refugees in Eastern Chad.

Abstract: Darfur refugees face hardships associated with chronic displacement, including lack of basic needs and safety concerns. Psychiatric research on refugees has focused on trauma, but daily stressors may contribute more to variance in distress. In this article we report rates of past trauma and current stressors among Darfur refugees and gauge the contribution of each to psychological distress and functional impairment. A representative sample of 848 Darfuris in two refugee camps were interviewed about traumatic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
110
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 153 publications
(127 citation statements)
references
References 31 publications
10
110
1
1
Order By: Relevance
“…It has been stated that post-flight experiences could be as important as pre-flight experiences in the development of psychiatric disorders among refugee children [32]. High prevalent rates of psychiatric disorders observed among refugee children must be evaluated because of a complex interaction between pre and post-flight experiences [33].…”
Section: Discussionmentioning
confidence: 99%
“…It has been stated that post-flight experiences could be as important as pre-flight experiences in the development of psychiatric disorders among refugee children [32]. High prevalent rates of psychiatric disorders observed among refugee children must be evaluated because of a complex interaction between pre and post-flight experiences [33].…”
Section: Discussionmentioning
confidence: 99%
“…Daily stressors have been found to be particularly salient for psychological distress in post-disaster and post-conflict settings such as Sri Lanka and Chad (Fernando, Miller, & Berger, 2010;Rasmussen et al, 2010). A study in Afghanistan found that high levels of daily stressors attenuated the relationship between war-related violence and depression/PTSD (Miller et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Above, one of the known mental health outcomes of exposure to war-related stressors is symptoms of posttraumatic stress [4], which include symptoms of avoidance. Above, daily stressors have been found to mediate the effects of war-related stressors [30] to produce posttraumatic stress reactions in victims. Since our study participants were exposed to a wide range of both war-related and daily stressors, it is not surprising that they also reported attitudes of avoidance.…”
Section: Discussionmentioning
confidence: 99%